Assessment of Vitamin D Level in a Sample of Iraqi Obese Women (Iraqi Journal of Medical Sciences, 2021)
Background: High prevalence of both vitamin D (vit. D) deficiency and obesity in world population as reported by many studies drown attention to establish the association and its direction between these two modifiable risk factors and their impact on health status which are still uncertain.Objective: To measure vit. D levels among a sample of obese women, describing some factors that may contribute for vit. D values in this sample and assess the correlation between vit. D levels and body mass index (BMI).Methods: A cross-sectional study was carried out among 100 obese women. Their age ranged between (20-50) years, during the period from 1st February to 1st August 2019. The sample was gathered from laboratory of private medical center at Palestine Street in Baghdad. vit. D was measured by (Ichroma vit D), which is a fluorescence immunoassay.Results: The mean±SD of vit. D values of the participants were found to be (16.05±6.9) ng/ml. Only two women from the sample had sufficient vit. D level of more than 30 ng/ml, (72%) of the participants found to have insufficient vit. D level 10-29.9 ng/ml and the remaining had deficiency in vit. D level
Keywords: Obese; women; vitamin D; body mass index